Alcohol use, suicidality and virologic non‐suppression among young adults with perinatally acquired HIV in Thailand: a cross‐sectional study. Issue 2 (13th February 2023) - Aurpibul, Linda; Kosalaraksa, Pope; Kawichai, Surinda; Lumbiganon, Pagakrong; Ounchanum, Pradthana; Natalie Songtaweesin, Wipaporn; Sudjaritruk, Tavitiya; Chokephaibulkit, Kulkanya; Rungmaitree, Supattra; Suwanlerk, Tulathip; Ross, Jeremy L.; Sohn, Annette H.; et al.
Abstract: Introduction: Young adults with perinatally acquired HIV (YA‐PHIV) are facing transitions to adult life. This study assessed health risk behaviours (including substance use), mental health, quality of life (QOL) and HIV treatment outcomes of Thai YA‐PHIV. Methods: A cross‐sectional study was conducted in Thai YA‐PHIV aged 18–25 years who were enrolled in a prospective cohort study at five tertiary paediatric HIV care centres in Thailand. Study data were obtained through face‐to‐face interviews from November 2020 to July 2021. Assessments were performed for alcohol use (Alcohol Use Disorders Identification Test; AUDIT), smoking (Fagerstrom Test for Nicotine Dependence), drug/substance use (Drug Abuse Screening Test; DAST‐10), depression (Patient Health Questionnaire for Adolescents; PHQ‐A), anxiety (Generalized Anxiety Disorder; GAD‐7) and QOL (World Health Organization QOL Brief‐Thai). HIV treatment outcomes were extracted from the National AIDS Program database. Results: Of 355 YA‐PHIV, 163 (46%) were males: their median age was 21.7 (interquartile range, IQR 20.2–23.5) years. There were 203 YA‐PHIV (58%) who reported ever having sex; 141 (40%) were sexually active in the past 6 months, of whom 86 (61%) reported 100% condom use. Overall, 49 (14%) met the criteria for harmful alcohol use; 28 (7.9%) were alcohol dependent. Sixty (17%) were current smokers and 37 (11%) used drugs/substances. The frequency of moderate up to severe symptoms for depression was 18% and for anxiety was 9.7%. Their overall QOL was good in 180 (51%), moderate in 168 (47%) and poor in five (1.4%). There were 49 YA‐PHIV (14%) with CD4 <200 cells/mm 3 and 85 (24%) with virologic non‐suppression (HIV‐RNA >200 copies/ml). On multivariate analyses, the highest education at the primary to high school or vocational school levels (adjusted odds ratio [aOR] 2.02, 95% CI 1.40–3.95, p 0.04), harmful alcohol use (aOR 2.48, 95% CI 1.24–4.99, p 0.01), alcohol dependence (aOR 3.54, 95% CI 1.51–8.31, p <0.01) and lifetime suicidal attempt (aOR 2.66, 95% CI 1.11–6.35, p 0.03) were associated with non‐suppression. Conclusions: Regular screening for alcohol use and mental health, including suicidality, would be useful to identify YA‐PHIV who need more intensive psychosocial support or referral services to ensure they can achieve and maintain a high QOL into adult life.